What to do when college is not the best time of your life - Leibow, David (Columbia University Press, 2010)
If college is supposed to be the best time of our lives, why are so many students unhappy? What causes a well-adjusted and academically successful high school graduate to suddenly flounder when he reaches college? Why might she start to binge on alcohol or engage in unsatisfying hook-ups? Where does the anger and self-doubt come from, and why is it directed at loving parents? Drawing on years of experience treating college-age youth, Leibow provides practice-based answers to these and other pressing questions. Instead of adventure, liberation, and a triumphant march into adulthoo.